2021
DOI: 10.3389/fmed.2020.606429
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Benefit of Remdesivir in COVID-19: A Systematic Review and Meta-Analysis

Abstract: Importance/Background: During current public health emergency of COVID-19 pandemic, repurposing of existing antiviral drugs may be an efficient strategy since there is no proven effective treatment. Published literature shows Remdesivir has broad-spectrum antiviral activity against numerous RNA viruses and has been recently recognized as a promising therapy against SARS-CoV-2.Methods: A systematic search was conducted for full length manuscripts published between inception and July 19th, 2020 focussing on effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…Aiswarya, et al found early initiation of remdesivir (within 48 hours of hospital admission) to be associated with 5.5 days decrease in the mean duration of hospitalization 25 . These results are consonant with what has been reported in the general population 15 , 16 , 39 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Aiswarya, et al found early initiation of remdesivir (within 48 hours of hospital admission) to be associated with 5.5 days decrease in the mean duration of hospitalization 25 . These results are consonant with what has been reported in the general population 15 , 16 , 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Anti-COVID-19 therapies such as hydroxychloroquine or ritonavir/lopinavir, are not used anymore, whereas pulse steroid therapy increases in consonance with the current scientific data 10 , 11 , 12 , 13 , 14 as well as remdesivir. Developed initially as a possible treatment for Ebola, remdesivir has shown promising results against SARS-CoV2 in reducing hospital stay and mortality 15 , 16 , 17 . However, a latter study has displayed no effect on hospitalized patients with COVID-19, as indicated by overall mortality, initiation of ventilation, and duration of hospital stay 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Nevertheless, in the multivariable analysis they performed, they did not account for the use for inpatient treatment agents that have been proven to modify outcomes in COVID-19 patients such as steroids, Remdesivir, and Tocilizumab. [36][37][38] IL-6 levels and Ddimer 39 , markers predictive of outcomes in COVID-19, were also not accounted for. As such, this increases the risk of a bias in their analysis of association between anticoagulation and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This virus belongs to the Coronaviridae family which also includes the severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1) and Middle East respiratory syndrome coronavirus (MERS-CoV). COVID-19 was declared as a pandemic by WHO on March 11th, 2020 [ 31 - 32 ]. Fever, myalgia, cough, dyspnea, and flu-like symptoms are the most frequent symptoms of COVID-19, which predominantly affects the respiratory system.…”
Section: Reviewmentioning
confidence: 99%